2022
DOI: 10.4314/tjpr.v20i8.14
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of anti-inflammatory and anti-ulcer properties of aerial parts of Centaurea tougourensis Boiss. and Reut.

Abstract: Purpose: To determine the anti-inflammatory and anti-ulcer properties of the aerial parts of Centaurea tougourensis Boiss. & Reut. Methods: The effects of n-butanol (n-BuOH) extract of the aerial part of Centaurea tougourensis on carrageenan-induced paw edema and ethanol-induced gastric mucosal damage were determined at 2 doses (200 and 400 mg/kg, po) in a mouse model. For each test, the animals were randomly divided into negative and positive control groups, as well as extract-treated groups. The mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Plants have demonstrated their ability to inhibit the proliferation of several tumor cell lines over time due to their abundance of bioactive compounds, particularly flavonoids, terpenoids, and saponins, which have a potent cytotoxic effect [59,60]. These classes of secondary metabolites have already been identified in C. tougourensis [61]. The ability of each compound to induce cytotoxicity on tumor cell line was investigated using CLC-Pred server and, as shown in Table 4, data clearly indicated that the four tested compounds expressed a moderate cytotoxic effect on the majority of cell lines evaluated in the present study.…”
Section: Cytotoxicity Predictionmentioning
confidence: 99%
“…Plants have demonstrated their ability to inhibit the proliferation of several tumor cell lines over time due to their abundance of bioactive compounds, particularly flavonoids, terpenoids, and saponins, which have a potent cytotoxic effect [59,60]. These classes of secondary metabolites have already been identified in C. tougourensis [61]. The ability of each compound to induce cytotoxicity on tumor cell line was investigated using CLC-Pred server and, as shown in Table 4, data clearly indicated that the four tested compounds expressed a moderate cytotoxic effect on the majority of cell lines evaluated in the present study.…”
Section: Cytotoxicity Predictionmentioning
confidence: 99%
“…However, the use of synthetic AChEI drugs is undesirably perceived by consumers due to their side effects, such as hypatotoxicity, gastro-intestinal disturbances, vomiting and diarrhea [ 1 ]. Furthermore, non-steroidal anti-inflammatory drugs (NSAIDs) are given as complementary treatment, but may present some drawbacks when used excessively during a long period of time due to the acquisition of drug resistance phenomenon, which underlines the urgent situation to develop more effective natural anti-inflammatory drugs with fewer undesirable effects [ 6 , 7 ]. Recently, there is a growing interest in studying medicinal plants in order to understand their full pharmacological potential along with preventing the development of chronic and degenerative diseases.…”
Section: Introductionmentioning
confidence: 99%